Depression and Associated Factors among Women having Primary Infertility (The Journal of Ad-din Women's Medical College, 2024)
Background: Depression is significantly higher in infertile women especially among women having primary infertility. The purpose of the study was to determine the level of depression and associated factors related to depression among women having primary infertility.Materials and Methods: This cross-sectional study was conducted from January to December 2022 with 165 women having primary infertility who were enrolled by convenience sampling technique from Dhaka Medical College and Hospital. A semi-structured questionnaire and checklist were used for data collection through face-to-face interview and reviewing medical records respectively. Data were analyzed by statistical software. Quality control and all ethical issues were strictly maintained in the study.Results: The mean age of women having primary infertility was 29.45 (±5.302) years. Out of 165 respondents, 160 (97%) showed depression. The majority 84(50.9%) had mild to moderate level of depression, while 49(29.7%) had moderate to severe depression. The mean duration of marriage was 8.48 (±4.78) years and the mean duration of getting treatment for infertility 2.33(±2.193) years. Among all, 113(68.5%) were trying to conceive for last 2-7 years and 59(35.75%) of the respondents had showed depression who faced negligence of husband for primary infertility and was statistically significant (p